Impact Of Sımbatan Communıty Manners About Covıd-19 Booster Vaccınatıons - Desi Kusumawati; Nabila Bintang Ramadhani; Puri Ratna Kartini (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Since Covid-19 pandemic begins in 2020 , the government has strive for reduce the spread of Covid-19. one of method for protect Public of the Covid-19 virus is with carry out the vaccination program.Success from the Covid-19 vaccination program seen from availability Public accept Lots of Covid-19 vaccinations issues about Covid-19 vaccinations that affect willingness community , such as security vaccine . Destination study this is for knowing influencing factors _ attitude Public about Covid-19 booster vaccination in the village Simbatan 2022. Research methods used _ is observational analytic with design study cross sectional .Data collected through Interview by direct use questionnaire . A total of 345 people Village Selected sympathizers _ by random participate in study ini.Analysis of the data used is regression logistics simple and regression logistics multiple . Research results show existence influence variable age ( p-value 0.001), education ( p-value 0.000) and marital status respondents ( p-value 0.000) to attitude Public about Covid-19 booster vaccination . Conclusion that there is influence factor predisposition to attitude Public about Covid-19 booster vaccination . Temporary that , no there is influence factor reinforcement and support to attitude Public about Covid-19 booster vaccination . because of it 's important for Keep going increase information about Covid-19 booster vaccine so that the public best understanding _ about vaccine and get increase confidence to vaccine have Covid-19.